Studi Komunitas Makrozoobenthos di Kawasan Hutan Mangrove Pulau Penyu, Tanjung Benoa, Bali - Faiqoh, Elok; Hayati, Henny; Yudiastuti, Kadek (Journal of Marine and Aquatic Sciences; Vol 2 No 1 (2016)DO - 10.24843/jmas.2016.v2.i01.23-28, 2016)
Mangrove in marine ecosystem have function to help continuing food chain directly, provide food for benthics organism, include macrozoo and microzoo, and ephiphyte  and indirectly as habitat, nursery ground and spawning ground (Nontji (1993), Valiela et al, (2001).  This research analyzed macrozoobenthics community in mangrove forest, Penyu Island, Tanjung Benoa, and counting correlation between mangrove density and macrozoobenthics abundance. 4 mangroves species ( Bruguiera gymnorrhiza, Rhizopora mucronata, Rhizopora stylosa dan Sonneratia alba ) and 22 macrozoobenthics genus ( Cvpraeidae, Naticidae, Cerithiidae, Mathildidae, Mitridae, Columbellidae, Buccinidae, Neritidae, Fasciolariidae, Smaragdinellidae, Littorinidae, Trochidae, Costellariidae, Terebridae, Opisthobranchia, Pyramidellomorpha, Littorinidae, Conidae, Thaididae, Potamididae, Turritellidae, Nassariidae ) were identified from 3 stasions over the Island. Rhizopora stylosa have the highest importance index in Penyu Island mangroves community and than Bruguiera gymnorrhiza . The highest abundance documented in station 1 for 385.2 ind/m 2 and then station 2 for 271.58 ind/m 2 and the lowest is station 3 247.71 ind/m 2 . Cerithium sp recorded as dominant species and Turritella cochlea and Cyprae kieneri as inferior species. Macrozoobenthos community in Penyu Island is being stable base d on high diversity index, moderate eveness index and low dominance index. The regression equation acquired Y = -60.524X + 119.94 and revealed correlation 40.05% and explain 16.04% macrozoobenthics varians. From the study inconclusive there are no correlation between mangroves density and macrozoobenthics abundance.
Keywords: macrozoobenhtics, mangroves, penyuisland , tanjung benoa